Characterization of humoral and cellular immune features of gamma-irradiated influenza vaccine. Issue 2 (1st February 2021) - Chen, Fengjia; Seong Seo, Ho; Ji, Hyun Jung; Yang, Eunji; Choi, Jung Ah; Yang, Jae Seung; Song, Manki; Han, Seung Hyun; Lim, Sangyong; Lim, Jae Hyang; Ahn, Ki Bum
ABSTRACT: The most widely used influenza vaccines are prepared by chemical inactivation. However, chemical, especially formalin, treatment-induced modifications of the antigenic structure of the virus are frequently associated with adverse effects including low efficacy of protection, unexpected immune responses, or exacerbation of disease. Gamma-irradiation was suggested as an alternative influenza virus inactivation method due to its great features of completely inactivating virus while not damaging the structures of protein antigens, and cross-protective ability against heterologous strains. However, immunological features of gamma radiation-inactivated influenza vaccine have not been fully understood. In this study, we aimed to investigate the humoral and cellular immune responses of gamma radiation-inactivated influenza vaccine. The gamma irradiation-inactivated influenza vaccine (RADVAXFluA ) showed complete viral inactivation but retained normal viral structure with functional activities of viral protein antigens. Intranasal immunization of RADVAXFluA provided better protection against influenza virus infection than formalin-inactivated influenza virus (FIV) in mice. RADVAXFluA greatly enhanced the production of virus-specific serum IgG and alveolar mucosal IgA, which effectively neutralized HA (hemagglutinin) and NA (neuraminidase) activities, and blocked viral binding to the cells, respectively. Further analysis of IgG subclasses showed RADVAXFluA -immunized sera had higher levels of IgG1 and IgG2a than those of FIV-immunized sera. In addition, analysis of cellular immunity found RADVAXFluA induced strong dendritic cells (DC) activation resulting in higher DC-mediated activation of CD8 + T cells than FIV. The results support improved immunogenicity by RADVAXFluA .